2018
DOI: 10.3168/jds.2017-14122
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Relationship between body condition score and plasma adipokines in early-lactating Holstein dairy cows

Abstract: We hypothesized that plasma adipokine concentrations of early-lactation dairy cows are related to body condition score (BCS) at calving and to markers of metabolic status of the cow. As part of a larger study with 117 multiparous Holstein dairy cows, which had high BCS (BCS >4.0) or normal BCS (3.25-3.5) at calving, 22 cows were randomly selected (n = 11 per group) to be enrolled in this study. Cows were divided into 2 groups based on their BCS at calving: (1) normal BCS with BCS of 3.35 ± 0.13 (mean ± SD) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the postpartum period Holtenius et al (2003), Mann et al (2018), andMansouryar et al (2018) did not find plasma leptin to be related to BCS. These results agree with our mRNA data and suggest that the volume of SAT has no effect on either the concen- Salin et al (2017) verified the hyperbolic relationship between insulin secretion and insulin sensitivity in dairy cows, which means that a change in sensitivity will be compensated by increased insulin secretion.…”
Section: Effects Of Bcs On Gene Expression In Satmentioning
confidence: 79%
“…In the postpartum period Holtenius et al (2003), Mann et al (2018), andMansouryar et al (2018) did not find plasma leptin to be related to BCS. These results agree with our mRNA data and suggest that the volume of SAT has no effect on either the concen- Salin et al (2017) verified the hyperbolic relationship between insulin secretion and insulin sensitivity in dairy cows, which means that a change in sensitivity will be compensated by increased insulin secretion.…”
Section: Effects Of Bcs On Gene Expression In Satmentioning
confidence: 79%
“…During the dry period of dairy cows, De Koster et al (2017) observed a negative correlation between body condition and serum adiponectin concentrations, with adiponectin values decreasing at the end of the dry period. However, comparing multiparous dairy cows with high (>4.0) and normal (3.25-3.5) BCS, body condition at parturition did not affect circulating adiponectin concentrations (Mansouryar et al, 2018).…”
Section: Fgf Receptormentioning
confidence: 81%
“…The proinflammatory cytokine IL-6, which regulates the hepatic synthesis of acute phase proteins, is positively related with NEFA and BHB at d 8 p.p. (Mansouryar et al, 2018) and is increased in ketotic cows (Loor et al, 2007;Rodriguez-Jimenez et al, 2018). Methylglyoxal (MGO), which is commonly used as a diagnostic parameter in diabetes type 2 in man, is significant higher in subclinical ketotic cows (1.2 mmol•l -1 ≥ BHB ≤ 3.0 mmol•l -1 ) and is positively correlated with acute phase protein haptoglobin in lactating cows (Li et al, 2018a).…”
Section: Ketosismentioning
confidence: 99%